Contactless tracking of humans using non-contact triboelectric sensing technology: Enabling new assistive applications for the elderly and the visually impaired. (December 2021) - Anaya, David Vera; Zhan, Ke; Tao, Li; Lee, Chengkuo; Yuce, Mehmet R.; Alan, Tuncay
Abstract: Continuous monitoring of human motion and its interaction with the surrounding environment is crucial for healthcare applications such as early diagnosis of neurological disorders, or rehabilitation of vulnerable patients with walking difficulties in hospital and age-care settings. Additionally, it is also necessary to provide assistive care to visually impaired individuals who are prone to falls. Commonly used wearable sensors require on-body components, which may cause discomfort. More importantly, the forgetfulness of people in hospital or aged-care settings or their resistance in using the on-body units, undermine the effectiveness of a wearable-based monitoring strategy. The ideal monitoring system should not interfere with the individual's privacy and daily routines and work continuously, without requiring any specific on-body devices. Here, we present a contactless sensing platform that can monitor and distinguish complex movements of human subjects, without requiring them to use wearable devices . The approach uses flexible Non-Contact Triboelectric Sensors (NCTS) (7 ×3.6 ×0.5 cm3) produced by attaching a negatively pre-charged PDMS film onto an aluminum (Al) foil. By exploiting the sensitivity to external electrostatic charges, near-field remote monitoring of human movements at distances as far as 1.5 m, is successfully achieved. Furthermore, The NCTS system differentiates activities such as walking, running, and jumping; and estimates walking speed, relative position, and direction of two people walking together in a contactless manner, which is not well examined in the literature of Non-contact Triboelectric Sensors, by analyzing the time domain and frequency spectrum of the output signal. Besides, the sensor is integrated with a portable accident prevention system designed to avoid visually impaired people's collisions with obstacles. Falling detection tests provide promising results for their application in elderly safety. Finally, indoor navigation/position monitoring and direction recognition are achieved and demonstrated using multiple NCTS, for future potential applications in elder activity tracking and people counting in hospitals. Graphical Abstract: ga1 Highlights: Non-Contact Triboelectric Sensor (NCTS) differentiates subject's walking, running, and jumping activities. Time-domain and frequency spectrum analysis estimate the speed and the relative walking direction of two people using NCTS. The NCTS is integrated into a wall-fixed and portable accident prevention system to assist blind people and the elderly. Multiple NCTSs are integrated for indoor navigation and walking direction monitoring for future elder activity tracking.